Strategi i navigation - Pedersen, Jacob Hald; Rasmussen, Thomas Eske (LexicoNordica, 2007)
When publishing in a new media the reasoning behind the choice of lemmata is affected. A popular strategy for navigation, full text retrieval, ensures that the reader finds his or her information. A new principle for navigating an encyclopaedia is topographical navigation. This approach is found in www.gyldendalsleksikon.dk which is an online information service including three different encyclopaedias. Here the reader can find articles through browsing pinpoints on a map of Denmark and via an implementation of the concept of mind map. These are two interesting alternatives to the traditional way of navigating an encyclopaedia.